PENGARUH DIFERENSIASI LAYANAN BRIS ONLINE DAN CITRA PERUSAHAAN TERHADAP KEUNGGULAN BERSAING PADA BANK BRI SYARIAH KCP MAGELANG - Hajar Mukaromah; Eka Yuli Kurniawati (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2021)
This study aims to determine how much influence the differentiation of BRIS Online services and the company's image on the competitive advantage of Bank BRI Syariah KCP Magelang. The population in this study were all customers who used BRIS Online services at Bank BRI Syariah KCP Magelang. The sample used was 103 respondents. The data analysis technique in this study used multiple linear regression methods using the SPSS version 17.0 application, with a quantitative descriptive field research approach. The results of this study indicate that simultaneously (together) the independent variables (BRIS Online service differentiation and company image) have a significant effect on the dependent variable (competitive advantage of Bank BRI Syariah KCP Magelang). While partially, the corporate image variable has a significant effect on the competitive advantage of Bank BRI Syariah KCP Magelang with a probability value of 0.000. Meanwhile, the differentiation variable of BRIS Online services partially has no effect on the competitive advantage of Bank BRI Syariah KCP Magelang with a probability value of 0.269. Meanwhile, the R2 value is 0.341 which indicates that the competitive advantage of BRI Syariah KCP Magelang can be explained by the research variable of 34.1%, while the rest is explained by other variables not examined in this study. For that, the company must maintain the existing corporate image so that the company is superior in competing.